The GDPR and the protection of the data subject between public and private enforcement in the case of cross-border processing - Scaffidi Runchella, Livio (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Regulation (EU) no. 2016/679 concerning the protection of individuals with regard to the processing of personal data, aims to ensure legal certainty and transparency for individuals and economic operators. The legal instrument offers the Member States of the European Union wide margins of procedural autonomy, particularly in situations of cross-border processing. For this reason, various problemsarise concerning jurisdictional competence, the relationship between concurrent proceedings whether they be of a civil or administrative nature, the relationship between the administrative remedy and the action for damages. The essay forms part of a very complex framework as new technologies constantly put the legislative process as well as the interpretation and application of the relevant legal provisions to the test.
Keywords: Processing of personal data; Regulation (EU) n. 2016/679; Jurisdiction; Supervisory authorities and judicial authorities